2002
DOI: 10.1139/z02-051
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal reproduction in the highveld mole-rat, Cryptomys hottentotus pretoriae (Rodentia: Bathyergidae)

Abstract: The highveld mole-rat, Cryptomys hottentotus pretoriae, is a cooperatively breeding rodent that exhibits seasonal breeding and a reproductive division of labour. Body mass, reproductive-tract morphometrics, ovarian histology, and plasma oestrogen and progesterone concentrations were studied for both reproductive and non-reproductive females from 55 colonies, the main objective being to determine the inclination of this species towards seasonal breeding. Offspring are born from July through to November. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 27 publications
1
67
0
Order By: Relevance
“…It is, however, noteworthy that within the more southerly occurring genus of Cryptomys, reproduction appears to be strictly seasonal, e.g. Cryptomys h. hottentotus (Spinks et al 1997(Spinks et al , 1999 and Cryptomys h. pretoriae (Janse van Rensburg et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, noteworthy that within the more southerly occurring genus of Cryptomys, reproduction appears to be strictly seasonal, e.g. Cryptomys h. hottentotus (Spinks et al 1997(Spinks et al , 1999 and Cryptomys h. pretoriae (Janse van Rensburg et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Common mole-rats were collected from Kamieskroon (30°S, 17°E, South Africa) and highveld mole-rats from the Pretoria area (26°S , 28°E, South Africa). From 2000 to 2002, entire colonies were trapped both during and out of the breeding season (i.e., the period in which mating, gestation, parturition, and lactation take place; Spinks et al, 1997Spinks et al, , 1999Janse van Rensburg et al, 2002). In the common mole-rat, pups are born from late November to January (Spinks et al, , 1999; the highveld mole-rat breeds from April to September (Janse van Rensburg et al, 2002).…”
Section: Study Animalsmentioning
confidence: 99%
“…These are the only social bathyergids known to restrict breeding to a particular season (Janse van Rensburg et al, 2002;Jarvis and Bennett, 1991); furthermore, in the subordinate colony members of these species, reproduction is suppressed throughout the year, as long as they remain within the confines of their natal colony (Bennett, 1989;Moolman et al, 1998). In female highveld mole-rats, the suppression of reproductive functions in the subordinates is associated with reduced pituitary sensitivity to GnRH ( Van der Walt, et al, 2001); this is not the case in the subordinate female common molerats (Spinks et al, 2000a).…”
mentioning
confidence: 99%
“…Georychus capensis, Bathyergus suillus, Bathyergus janetta and Heliophobius argenteocinereus (Sumbera et al 2003;Hart et al 2006;Oosthuizen & Bennett 2007), and social, e.g. Cryptomys and Fukomys (Bennett & Jarvis 1988a;Bennett 1989;Burda 1989;Spinks et al 1997Spinks et al , 1999Janse van Rensburg et al 2002. Until recently, the only published information on the reproduction of the giant mole-rat was derived from laboratory studies (Bennett & Aguilar 1995;Scharff et al 1999) and one small field study (Scharff et al 2001) in which reproduction was suggested to take place throughout the year, or from anecdotal reports from Ansell (1978) who captured young animals throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…To date, all the studied species within the genus Fukomys have been reported to be aseasonal breeders producing offspring throughout the year: F. damarensis (Bennett & Jarvis 1988a,b;Bennett & Faulkes 2000), F. darlingi (Bennett et al 1994) and F. anselli (Burda 1989) By contrast, within the more southerly occurring genus Cryptomys, reproduction appears to be more seasonal, e.g. Cryptomys h. hottentotus (Spinks et al 1997(Spinks et al , 1999 and Cryptomys h. pretoriae (Janse van Rensburg et al 2002).…”
Section: Discussionmentioning
confidence: 99%